Abundance and Diversity Index of Weeds in Oil Palm and Vegetable Intercropping in Rainforest Zone of Nigeria - Ayodele Samuel Oluwatobi; Kehinde Stephen Olorunmaiye (Universitas Sebelas Maret, 2021)
The problem of severe weed infestation often arises during the early phases of establishment of oil palm field due to the spacing requirement and growth habit of young oil palm plantation until later years when the canopy closes. This study was conducted at Ala, Akure-North Local Government Area, Ondo State, Nigeria, to investigate the composition of weed species and their distribution in fruit vegetable-juvenile oil palm intercrop. The fallow alleys within the immature oil palm were intercropped with 2 accessions of tomato (NGB 01665 and NG/AA/SEP/09/053) and eggplant (NGB 01737). The sampling of the weed species was carried out with a quadrat (0.25 m2). Weed species parameters and the Diversity Index (D) were quantitatively analyzed. The results revealed that members of Asteraceae and Poaceae gave the highest weed species at 3 and 6 weeks after intercropping (WAI) (17.857% and 19.04%) respectively. A total of 23 and 16 were found at 3 and 6 WAI, while the least diversity index of 0.734 was recorded in the immature oil palm/tomato (NGB 01665) plot at 6 WAI. Farmers should be persuaded to simultaneously intercrop fruit vegetables within the alley of juvenile oil palm, particularly at the earlier years prior to closure of the oil palm canopy.